Distribution and determinants of the utilization of senior residential care homes in Saudi Arabia: a cross-sectional study - Bindawas, Saad M.; Vennu, Vishal; Almarwani, Maha; Alkeridy, Walid (Frontiers in Public Health, 2025)
BackgroundWith the accelerated increase in the population of seniors aged 60 years or older in Saudi Arabia, understanding the utilization of senior residential care homes is crucial for improving service delivery and policy planning to meet the care transformation objectives of Vision 2030.ObjectiveTo assess the distribution and determinants of senior residential care home utilization across Saudi Arabia’s 13 administrative regions, focusing on predictors of functional dependency among different socio-demographic groups.MethodsThis study analyzed data from 283 Saudi individuals aged ≥65 admitted to social residential care homes in 2021. Variables included age, sex, education level, marital status, region, and reasons for service use. Statistical analyses comprised descriptive statistics, chi-square tests, independent t-tests, and multivariable logistic regression.ResultsThe Makkah region had the highest number of senior residential care home users (56.8%; p < 0.0001). Most participants were men (67.8%), while women constituted 32.2%. The mean age was 78.9 years (SD = 10.6), with women being significantly older than men (p = 0.014). Illiteracy was prevalent (73.5%), particularly among women (82.4% vs. 69.3% for men; p = 0.006). Most participants were divorced (68.2%), with higher rates among men (84.9% vs. 33% for women; p < 0.0001). The primary reasons for utilizing residential care home services were old age and functional dependency (88.5% of men and 83.4% of women). Multivariable logistic regression indicated that being in the age group 75–84 years (odds ratio [OR] = 1.62, 95% confidence interval [CI] = 1.02–1.81, p < 0.001), 85 years and above (OR = 2.63, 95% CI = 1.28–3.11, p < 0.001), and being single (OR = 2.43, 95% CI = 1.14–5.13, p = 0.019) were significant predictors of old age and functional dependency.ConclusionThe study highlights regional and socio-demographic variations in senior residential care home service utilization in Saudi Arabia, emphasizing the need for targeted interventions and policies aligned with Saudi Arabia’s Vision 2030 to enhance service accessibility and effectiveness for the aging population.